The Effect of Prenatal Stress on a Mouse Model of Allergic Airway Disease - Chau, Jessie T. (My University, 2013)
Prenatal life events have been long observed to be able to influence disease into adulthood in both epidemiological and animal studies. Prenatal stress (maternal stress during gestation) is one of such factors that has been shown to impact cognition and behaviour of the offspring. However, the effects of prenatal stress on the immune system are not understood. This study has evaluated the effects of prenatal stress on a murine model. Prenatal stress increased allergic airway inflammation in male, but not female offspring following sensitization and challenge with cockroach extract. This corresponded with stress-induced changes in the immune environment of non-sensitized animals. These changes included a decrease in regulatory T cells at baseline in males compared to non-stressed controls and increased splenic dendritic cell percentage and cytokine, particularly IFN-γ, secretion compared to prenatally stressed females. In females, prenatal stress decreased allergic inflammation, which corresponded to a decreased percentage of dendritic cells in the lung and mesenteric lymph node. Prenatal stress did not affect dendritic cell antigen presentation in ether male or female offspring. There was no evidence to suggest a prenatal stress induced change in glucocorticoid sensitivity of dendritic cells. In order to explore the possibility of prenatal stress induced decrease of parasympathetic output, a vagotomy model was used as a proof of concept in naïve animals not exposed to prenatal stress. Vagal modulation of dendritic cell phenotype and function was assessed. While there was some evidence that vagotomy may indirectly modulate dendritic cell function, its effects on the immune system were different then the changes caused by prenatal stress and thus it is a role of reduced parasympathetic output was not supported. Overall this data indicates a role of prenatal stress on the immune system with clear sex differences, but the mechanism for how this occurs is currently unknown. Further research is needed to investigate the role of TLRs and IFN-γ in this model, as well as other possible mediators of prenatal stress such as the changes to the parasympathetic nervous system that may in turn mediate alterations to the immune system. Differences in when the effects of prenatal stress are expressed during postnatal life are discussed.
Keywords: Prenatal Stress; Allergic Airway Disease; Mouse Model; Immunopathology; Medical Immunology; Immunopathology